Pengaruh Kompensasi, Motivasi, Dan Lingkungan KerjaTerhadap Kinerja Pegawai Rsud Pandan ArangBoyolali - Yuniati, Arifah, Drs. Yuli Tri Cahyono , M.M., Akt., CA (2015)
Employees performance is one of the elements that can affect the sustainability of an institution. Appropriate compensation, good motivation, and a supportive work environment can improve employees performance and institution's sustainability. This research purposes to examine and analyze the influence of compensation, motivation, and work environment on employees performance at RSUD Pandan Arang Boyolali. The amount of the sample in this research is 69 employees. The sampling techniques in this research uses purposive sampling method. The data analysis in this research uses the help of SPSS version 15. The analysis method that is used is multiple linear regression to test and prove the research hypothesis. The analysis showed that compensation, motivation, and working environment have a significant effect on employee performance. This can be seen from the value tcount > ttable and the probability of < 0,05. Keywords:compensation, motivation, work environment, employee performance.